(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to determine the role of local governments in promoting Tanjung Baong tourism objects in Soasio Village, Galela Subdistrict, North Halmahera Regency, which are reviewed in planning in promoting an object and implementing and evaluating. Promoting tourism objects aimed at attracting tourists who come by sebap that there must be clear information and the government must also have a strategy to influence tourists to be interested and interested in visiting these attractions. The role of blood government is very important to realize the wishes of the village government and the community to introduce Tanjung bongo out and to be better known by the outside community. This study uses qualitative research methods adapted to the title and the problem of the research objective is to determine the role of local governments the success of local governments in increasing tourist visits can run well. Keywords: The Role of Government Object Promotional Regional Promotion